Vadianus, Joachim - McDonald, G (Springer, Cham, 2020)
Joachim Vadianus (von Watt) was a significant representative of Viennese humanism and Lutheran reformer of St Gallen. His writings fall roughly into two groups: literary and scientific works from Vienna, written in Latin for the university and the court; and Reformation writings from St Gallen, mostly in German.